Intertrochanteric femoral fracture after hip resurfacing managed with a reverse distal femoral locking plate: a case report - Baxter, Jonathan A; Krkovic, Matija; Prakash, Udai (Hip international, 2010)
Metal-on-metal hip resurfacing is a popular procedure for a select group of patients. A variety of surgical approaches are being utilised, each of which may be associated with specific complications. We describe an unusual complication following a Ganz trochanteric osteotomy approach, and the technique used to treat the subsequent periprosthetic fracture.